PELATIHAN TRAUMA HEALING BAGI AKTIVIS DAN RELAWAN PERLINDUNGAN ANAK TERPADU BERBASIS MASYARAKAT - Azriadi Tanjung; Sriayu Aritha Panggabean (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of implementing this community partnership program (PKM) service is (1) to minimize the impact of killing characters on children (2) to assist the Sibolga City Government in providing information and knowledge to the community, especially the families of victims of child violence in Sibolga City in early psychological handling of victims ( 3) educating the public on prevention and early detection of the psychological condition of children as victims of violence (4) giving birth to trauma healing counselors in the Sibolga City community who can reduce the number of violence against children by changing social norms and cultural practices in society (5) building systems at the level of communication and family in preventing violence. The method of implementing training activities for Community-Based Integrated Child Protection Activists and Volunteers includes 3 stages, namely: (1) Training Preparation Stage, (2) Training Implementation Stage, (3) Final Evaluation Stage. PKM's community service partners are the Sub-District Community Empowerment Office, Women's Empowerment, and Child Protection in Sibolga City. This program is implemented as an effort to produce trauma healing counselors in the Sibolga City community who can reduce the number of violence against children by changing social norms and cultural practices in society. This activity also aims to enable Community-Based Integrated Child Protection Activists and Volunteers to assist the Sibolga City Government in providing information and knowledge to the community, especially the families of victims of child violence in Sibolga City in early psychological treatment of victims. It is hoped that this program will run well and the knowledge of the community will increase. The expected outcome of this mentoring program is the publication of scientific papers in national proceedings and journals with ISSN. Keywords: Trauma, Healing, Training